ANALISIS PELAKSANAAN TUGAS POKOK DAN FUNGSI (TUPOKSI) UPT MUSEUM SANG NILA UTAMA DI KOTA PEKANBARU - Mohammad Joko Suryo; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation Analysis of Main Duties and Functions (TUPOKSI) UPT Sang Nila Utama Museum in the city of Pekanbaru . The purpose of this study is to analyze pelasanaan duties and functions and to analyze the factors that affect the implementation of the duties and functions UPT Sang Nila Utama Museum in the city of Pekanbaru . This study uses the theory Suprihartono Jhon who explained that the implementation of the tasks measured : task mastery , ability to cooperate , ability to complete work on time and work reports the right . The research method is qualitative observation techniques and interviews with key informants as key informants and snowball sampling method in the determination of subsequent informants and analyzed using descriptive analysis techniques . The results of this study are the duties and functions of UPT Sang Nila Utama Museum in the city of Pekanbaru is not operating effectively . Human Resources required by Sang Nila Utama Museum UPT still inadequate especially sexy and development management . Care facilities in a state of cultural heritage objects is not good . Coordination and promotion of Sang Nila Utama Museum UPT with other Government agencies are not running optimally .Kata kunci: Analisis, Pelaksanaan Tugas, dan Organisasi